Reviving Nature's Guardians: Linking Landscape Restoration to Climate Change Mitigation - Charry Mae Sedoro Numeron; Evelyn V. Bigcas; Nelieta A. Bedoya (SEAMEO BIOTROP, 2023)
This comprehensive paper navigates the complexities of climate change mitigation and adaptation, unraveling challenges across scales and suggesting innovative solutions. It delves into indicators, tools, and methods that empower policymakers and practitioners, offering a roadmap for effective strategies. Through synthesizing literature and real-world cases, it sheds light on climate change intricacies, urging collaborative efforts and innovative approaches. The findings empower readers with actionable insights to drive impactful climate changemanagement.